Monocyte/High-Density Lipoprotein Ratio Predicts the Prognosis of Large Artery Atherosclerosis Ischemic Stroke - Li, Youyu; Chen, Daqing; Sun, Laifang; Chen, Zhibo; Quan, Weiwei (Frontiers in Neurology, 2021)
Objective: Monocyte to high-density lipoprotein ratio is considered as a new inflammatory marker and has been used to predict the severity of coronary heart disease and the incidence of adverse cardiovascular events (ACEs). However, there is a lack of data relative to large artery atherosclerosis (LAA) ischemic stroke. We investigated whether the monocyte to high-density lipoprotein (HDL) ratio (MHR) is related to the 3-month functional prognosis of LAA ischemic stroke. Materials and Methods: A retrospective analysis was conducted on 316 LAA ischemic stroke patients. The 3-month functional outcome was divided into good and poor according to the modified Rankin Scale (mRS) score. Multivariate logistic regression analysis was performed to evaluate the correlation between MHR and prognosis of ischemic stroke. Results: The MHR level of poor functional outcome group was higher than that of the good functional outcome group [0.44 (0.3, 0.55) vs. 0.38 (0.27, 0.5), P = 0.025]. Logistic stepwise multiple regression revealed that MHR [odds ratio (OR) 9.464, 95%CI 2.257–39.678, P = 0.002] was an independent risk factor for the 3-month poor outcome of LAA ischemic stroke. Compared to the lower MHR tertile, the upper MHR tertile had a 3.03-fold increase (95% CI 1.475–6.225, P = 0.003) in the odds of poor functional outcome after adjustment for potential confounders. Moreover, a multivariable-adjusted restricted cubic spline (RCS) showed a positive close to a linear pattern of this association. Conclusion: Elevated MHR was independently associated with an increased risk of poor 3-month functional outcome of patients with LAA ischemic stroke.